2015
DOI: 10.1007/s13187-015-0889-x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Learning Environment in Continuing Education for Nursing in Oncology: an Experimental Study

Abstract: Nurses working in oncology require continuing education and nowadays distance education is a possibility. To compare learning outcomes of the professionals participating in classroom learning versus distance learning; describing the sociodemographic characteristics and digital fluency of participants; comparing learning outcomes with independent variables; assessing the adequacy of educational practices in Virtual Environment Moodle Learning through the constructivist online learning environment survey. An exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
4
0
6
Order By: Relevance
“…Dentre os estudos que utilizaram testes estatísticos como procedimento de análise de dados, 24 aplicaram questionários de pré e de pós-teste com o objetivo de avaliar diferentes aspectos dos cursos, com destaque para a avaliação do ganho de conhecimento (BRESSEM et al, 2016;MCLEOD;MORCK;CURRAN, 2014;LAVENDER et al, 2013;MOREIRA et al, 2015;MICHELAZZO et al, 2015;KULIER et al, 2012;ILOTT et al, 2014;BROWNLOW et al, 2015;WANG et al, 2016;BLAZER et al, 2012;KENEFICK et al, 2014;CHO;SHIN, 2014). Instrumentos de pré e de pós-teste também incluíram perguntas relacionadas às características sociodemográficas dos participantes (BRESSEM et al, 2016;MCLEOD;MORCK;CURRAN, 2014;MOREIRA et al, 2015; O'BRIEN; BROOM; ULLAH, 2015; MATSUBARA; DOMENICO, 2016).…”
Section: Atitudesunclassified
See 1 more Smart Citation
“…Dentre os estudos que utilizaram testes estatísticos como procedimento de análise de dados, 24 aplicaram questionários de pré e de pós-teste com o objetivo de avaliar diferentes aspectos dos cursos, com destaque para a avaliação do ganho de conhecimento (BRESSEM et al, 2016;MCLEOD;MORCK;CURRAN, 2014;LAVENDER et al, 2013;MOREIRA et al, 2015;MICHELAZZO et al, 2015;KULIER et al, 2012;ILOTT et al, 2014;BROWNLOW et al, 2015;WANG et al, 2016;BLAZER et al, 2012;KENEFICK et al, 2014;CHO;SHIN, 2014). Instrumentos de pré e de pós-teste também incluíram perguntas relacionadas às características sociodemográficas dos participantes (BRESSEM et al, 2016;MCLEOD;MORCK;CURRAN, 2014;MOREIRA et al, 2015; O'BRIEN; BROOM; ULLAH, 2015; MATSUBARA; DOMENICO, 2016).…”
Section: Atitudesunclassified
“…Nos questionários aplicados antes e após a intervenção do curso de formação profissional foram solicitadas informações relacionadas à experiência na área do curso (BRESSEM et al, 2016;MATSUBARA;DOMENICO, 2016), metas em relação ao curso (BRESSEM et al, 2016), tempo previsto para dedicação ao…”
Section: Atitudesunclassified
“…Tiffany Bryant, DNP, RN-BC, PCCN; and Laurie Posey, EdD routinely gather end-of-course evaluation data, and substantive evidence suggests that CE increases participants' knowledge related to the intended learning objectives (das Graças Silva Matsubara & De Domenico, 2016;De Gagne et al, 2015;Yacoub et al, 2015); however, little generalizable research focuses on the transfer of CE to nursing practice.…”
Section: Evaluating Transfer Of Continuing Education To Nursing Practicementioning
confidence: 99%
“…Delivery of cancer education around the globe tends to be through flexible blended formats, which include didactic, face-to-face, practice and interactive learning using video and other media formats to accommodate working professionals (Cable and Parr, 2009, Edwards et al, 2016, Jestico and Finlay, 2017). There has also been a growth in the Virtual Learning Environment (VLE) as this enables teaching, learning and assessing to be delivered on line and is desirable for learners who cannot access modules/courses due to geographical reasons (Cable and Pettit, 2012, das Graças Silva Matsubara et al, 2016, Lahti et al, 2014, Voutilainen et al, 2017. It also offers a more flexible way of engaging with the materials and is a more accessible way of learning for busy practitioners with varied working patterns (Cable and Parr 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It also offers a more flexible way of engaging with the materials and is a more accessible way of learning for busy practitioners with varied working patterns (Cable and Parr 2009). One study that compared the learning outcomes of 148 nursing professionals who participated in classroom learning versus distance learning found that VLE education to be an effective alternative for educating and training nurses (das Graças Silva Matsubara et al (2016). However, future resources should consider developing materials for an international market so that education and good practice can be shared (Edwards et al, 2016, Jestico andFinlay, 2017).…”
Section: Introductionmentioning
confidence: 99%